Alternatives to common approaches for training change of direction performance: a scoping review - Buhmann, R.; Stuelcken, M.; Sayers, M. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Background Research focuses heavily upon the effect of strength and power training on change of direction performance. The objective of this scoping review is to highlight alternative approaches to training change of direction.